Detection of Chlamydia pneumonia and Mycoplasma pneumonia in hospitalised children with community acquired pneumonia - Ramamoorthy, Kannan; Sundaram, Agora Shivan Shanmuga (International Journal of Contemporary Pediatrics, 2018)
Background: Mycoplasma pneumoniae and Chlamydia pneumoniae are atypical pathogens responsible for community acquired pneumonia (CAP) and are a leading cause of morbidity and mortality in low income countries. The study objective was to determine the prevalence of C. pneumoniae and M. pneumonia in hospitalized children with CAP. Methods: This study was performed on ninety-four children admitted with radiologically confirmed diagnosis of pneumonia in Government Rajah Mirasudar Hospital, Thanjavur, during the period of July 2005 to April 2006. The diagnosis of infections with C. pneumonia and M. pneumonia was determined by detection of IgM antibody by using ELISA method. In this study clinical and radiological feature of these infections were also looked for. Results: Among 94 children, 9 children (9.6%) were detected positive for M. pneumonia and 8 children (8.5%) were detected positive for C. pneumonia. Infection rate was highest among 5-12 years and least among 1 month to 24 months age group. The most common symptoms observed in patients with these pathogens are cough, fever, crepitations and rhonchi. Pulmonary infiltrates were the most common chest X-ray features of both C. pneumoniae pneumonia and M. pneumoniae pneumonia. Conclusions: This study has shown that C. pneumonia and M. pneumonia play a significant role in paediatric CAP. Identification and confirmation of these organisms by IgM ELISA helps in better management that would decrease the need for hospitalization and IV antibiotics.